Trusting local translation: Experiences from transplanting a 'Made in Britain' entrepreneurship course in China. Issue 2 (April 2014) - Farquharson, Maris; Örtenblad, Anders; Hsu, Shih-wei
As export education is destined to be one of the new growth industries, an entrepreneurship course designed in the United Kingdom is exported to China. We reflect on the transplantation of entrepreneurship theory. Knowledge as it travels becomes decontextualised, but by relying on actor–network theory, we find that knowledge multiplies. Students in China were able to contextualise knowledge to fit with local circumstances. Relying on a single case study, narratives were shared by Chinese students exposed to the same entrepreneurship course. We identified artefacts, people, institutions and relationships in social-networks translating student realities of learning entrepreneurship. Their narratives revealed translation to be rooted in power struggles and historical and familial constructs. Contrary to the expectations of previous studies, there may be no need for teachers to contextualise course content. Students are capable of doing this. Teachers can therefore trust in local translation.